Kajian Etnosains pada Pudak Khas Gresik: Pelestarian Kearifan Lokal - Fitriyani, Anik; Safitri, Yohana; Arbiana, Barika; Roqobih, Fikky Dian; Subekti, Hasan (Universitas Sarjanawiyata Tamansiswa, 2023)
Pudak is a dish that is traditionally eaten in Gresik, East Java, and has become a living record of the city's evolution through the years. Pudak possesses numerous excellent Gresik qualities and features that should be conserved because it is the indigenous wisdom of the city. An understanding of science, or information that can be replicated and is acknowledged by the scientific community, also known as ethnoscience, must be linked to the preservation of local wisdom values. The process of integrating cultural norms and traditions with scientific knowledge is known as ethnoscience. The traditional Pudak meal typical of Gresik City was the subject of an ethnoscientific study, which tries to represent indigenous knowledge of the community with scientific understanding. Research data for this study were gathered from linked research publications and exploratory activities utilizing a qualitative methodology based on ethno-science studies. The